Modelo matemático para el control de la transmisión del Dengue. - López, Luis E.; Muñoz-Loaiza, Aníbal; Olivar-Tost, Gerard; Betancourt-Bethencourt, José (Revista de Salud Pública)
Objective A mathematical model is presented in this paper showing the dynamics of dengue transmission. The goal was to study Aedes aegypti population behaviour and that of affected people to scientifically support the decision-making involved in surveillance and control programmes. Methods The proposed mathematical model involved eight differential equations having constant delays; each represented each population's variation either in humans or the mosquito vector. Results Two of the mathematical model's simulation scenarios are presented; they were solved by means of an algorithm implemented in MATLAB software. The data was obtained from the Colombian Statistics Department (DANE), the World Health Organisation (WHO) and from a review of the pertinent literature. The data regarding human and vector populations was analysed (with and without using controls). Conclusions The proposed mathematical model was able to simulate the dynamics of dengue transmission; it simulated the population-related behaviour of Aedes aegypti and the affected people. This model could be a tool for scientifically supporting surveillance and control programmes' decision-making.